Resilient Communities and the Peccioli Charter
XX, 275 p. 100 illus., 79 illus. in color.
Keywords: This book explores urban resilience through significant, original and rigorous academic research, utilising the experiences of town planners, architects and decision makers to create a charter on resilient communities. The second part of the book presents mini-essays discussing the strategic points of the paper, and enabling more casual readers with the ability to access information on urban resilience. The book then explores urban resilience through the work and understanding of the institutions responsible for regulating the professions of urban planner, educators, professionals, and those involved in communication. Providing numerous illustrations and examples, Resilient Communities and the Peccioli Charter will be of interest to researchers, postgraduates, architects, urban designers and planners alike.